Deciphering the link between salicylic acid signaling and sphingolipid metabolism - Sánchez-Rangel, Diana; Rivas-San Vicente, Mariana; de la Torre-Hernández, M. Eugenia; Nájera-Martínez, Manuela; Plasencia, Javier (Frontiers in Plant Science, 2015)
The field of plant sphingolipid biology has evolved in recent years. Sphingolipids are abundant in cell membranes, and genetic analyses revealed essential roles for these lipids in plant growth, development, and responses to abiotic and biotic stress. Salicylic acid is a key signaling molecule that is required for induction of defense-related genes and rapid and localized cell death at the site of pathogen infection (hypersensitive response) during incompatible host-pathogen interactions. Conceivably, while levels of salicylic acid rapidly increase upon pathogen infection for defense activation, they must be tightly regulated during plant growth and development in the absence of pathogens. Genetic and biochemical evidence suggest that the sphingolipid intermediates, long-chain sphingoid bases and ceramides, play a role in regulating salicylic acid accumulation in plant cells. However, how signals generated from the perturbation of these key sphingolipid intermediates are transduced into the activation of the salicylic acid pathway has long remained to be an interesting open question. At least four types of molecules –MAP kinase 6, reactive oxygen species, free calcium, and nitric oxide– could constitute a mechanistic link between sphingolipid metabolism and salicylic acid accumulation and signaling.